Nocturnal Mean Oxygen Saturation Is Associated with Secondary Polycythemia in Young Adults with Obstructive Sleep Apnea, Especially in Men - Li N (Dove Medical Press, 2019)
Ning Li,1,2,* Hong Peng Li,1,2,* Ping Wang,1,2 Ya Ru Yan,1,2 Shi Qi Li,1,2 Qing Yun Li1,2 1Department of Respiratory and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Institute of Respiratory Disease, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing Yun LiDepartment of Respiratory and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, No. 197 Ruijin 2nd Road, Shanghai 200025, People’s Republic of ChinaTel +86-21-64370045Fax +86-21-57643271Email liqingyun68@hotmail.comObjective: Whether the severity of obstructive sleep apnea (OSA) contributes to clinical polycythemia is uncertain, especially in young adults. This study aimed to assess the correlation between untreated OSA and polycythemia, controlling for multiple confounders, and to observe the difference in both genders.Methods: All participants underwent nocturnal polysomnography. Medical comorbidities, and demographic and laboratory information were also recorded. The relationship between OSA and concomitant polycythemia in both genders was analyzed.Results: A total of 605 young participants (383 men and 222 women), aged 30.52 ± 7.21 years, were enrolled, with an average body mass index of 32.48 ± 6.06 kg/m2. Although 74.4% of patients were diagnosed with OSA, less than 10% had polycythemia. The levels of hemoglobin and hematocrit increased with the severity of OSA; only men with severe OSA had significantly higher hemoglobin, hematocrit, and polycythemia compared with those in the control group (P < 0.01). Hemoglobin and hematocrit significantly correlated with mean pulse oxygen saturation (SpO2) (P < 0.001), but the correlation coefficients were weaker in women than in men. In logistic regression analysis, mean SpO2, but not the apnea–hypopnea index (AHI), was found to be an independent predictor of polycythemia (P < 0.05). Areas under the receive operator characteristic analysis revealed that the cutoff values of hemoglobin and hematocrit were 155.5g/L and 44.6% (P < 0.001), respectively, for assessing nocturnal hypoxemia in men with OSA.Conclusion: Nocturnal mean SpO2 was an independent predictor of polycythemia in young adults. Mean SpO2, compared with the AHI, was more associated with polycythemia. Men were more prone to suffer from polycythemia compared with women. Hemoglobin and hematocrit values might have diagnostic utility for assessing nocturnal hypoxia severity of OSA patients, especially in men.Keywords: obstructive sleep apnea, nocturnal hypoxia, polycythemia, erythropoiesis, biomarker